Corporate Governance and Market Base Performance of Commercial Banks of Nepal - Sapkota, Mohan Prasad; Poudel, Omkar (BMC Journal of Scientific Research, 2022)
Corporate governance contains the rules, regulations, system, code of conduct and procedures for proper management and operation of the firm. This study is focus on examining the ascendency of CG on market base performance of Nepalese banks measured by Tobin’s Q. The population of the study is the total number of ‘A’ grade banks licensed by Nepal Rastra Bank is 27 till January, 2021.The samples of the study were twelve commercial banks. Corporate governance is measured by LR, B Size, B Meeting and OWC. The mediating variables of the study are CAR, F SIZE, and NIM. This study basically utilized multiple regression analysis and found that LR, OWC, NIM and CAR have significant positive influence on performance measured by Tobin’s Q. However, B Meeting and B Size had significant negative influence on performance. Evidence suggests that corporate governance significantly influences the market base financial performance of Nepalese commercial banks measured by Tobin’s Q. Finally, Nepalese commercial banks can ensure their superior market base financial performance by enhancing effective corporate governance practices.